Evidence of Manager Intervention to Avoid Working Capital Deficits - Dyreng, Scott D.; Mayew, William J.; Schipper, Katherine (Contemporary Accounting Research, 2017)
Abstract We study managers’ interventions in financial reporting by examining working capital deficits, measured as current ratios less than 1.0. Current ratios represent important balance sheet liquidity indicators to lenders and creditors, and have an identifiable and naturally occurring reference point at 1.0, analogous to the profit/loss income statement reference point. We find that distributions of reported current ratios of both U.S. and non‐U.S. firms exhibit a discontinuity at 1.0. For U.S. firms, we find that the discontinuity increases with exogenous increases in the cost of credit in the economy, and that determinants of the likelihood to achieve a given current ratio are diagnostic precisely at the 1.0 discontinuity location but not at other nearby locations in the current ratio distribution. U.S. firms that avoid working capital deficits report lower proportions of inventory and higher proportions of accounts receivable in current assets and, when credit is tight, higher proportions of cash, consistent with managers increasing sales volume so as to capitalize profit margins and thereby increase current assets. For non‐U.S. firms, the discontinuity is more pronounced for observations from common law countries, a proxy for jurisdictions where financial reports are more intended to provide decision‐useful information. The evidence suggests that managers intervene to achieve a balance sheet reporting objective that stems from stakeholder use of reference points.